Syair Berbahasa Persia dalam Kitab Ta’lim Al-Muta’allim - Hilal, Muhammad (Proceedings of Annual Conference for Muslim Scholars, 2023)
Numerous studies have been conducted regarding the poems found in Burhān ad-Dīn az-Zarnūjī’s book entitled Ta‘līm al-Muta‘allim, yet none of them specifically investigate a Persian poem within the book. Furthermore, the composition of this Persian poem, particularly in printed copies of Ta‘līm al-Muta‘allim circulated in Indonesia, supposedly has errors in its encryption making them not easy to read and to translate literally. The purpose of this research is to uncover these encryption inaccuracies and to explore ways to accurately read and translate them, enabling the readers in Indonesia, especially readers in the pesantren community, to be aware of these encryption errors and to read them correctly. The research employs library research method, underpins a qualitative approach, and uses the analytical model offered by Merriam and Tisdell. This investigation has disclosed that nearly all printed versions of Ta‘līm al-Muta‘allim contain wrong renditions of the Persian poem, with the exception of those printed in Istanbul and Karachi. The encryption errors consist of (1) inaccuracies in writing letters, (2) misplacements of spacing, and (3) errors in diacritical marks of vowels.